Carboxyhemoglobin as a diagnostic and prognostic biomarker of hemolytic anemias in dogs. (26th December 2022) - Nivy, Ran; Sutton, Gila; Bruchim, Yaron
Abstract: Background: Endogenous production of carbon monoxide during hemoglobin metabolism leads to the formation of carboxyhemoglobin. Carboxyhemoglobin concentration is abnormally high in humans with hemolytic anemia (HA). Hypothesis: Measurement of carboxyhemoglobin concentration can discriminate HA from other forms of anemia. Animals: Twenty‐seven dogs with HA (immune‐mediated HA, n = 22; microangiopathic HA, n = 5), 27 dogs with non‐HA (kidney disease, n = 14; immune‐mediated thrombocytopenia, [n = 6]; miscellaneous, n = 7) and 24 nonanemic control dogs. Methods: Prospective cohort study. Carboxyhemoglobin quantification, a CBC and biochemistry profile were performed upon admission, and survival to hospital discharge and at 30 days were the measured outcomes. Groups were compared by the Mann‐Whitney and Kruskal‐Wallis tests. Receiver‐operator characteristic (ROC) analyses were used to examine the predictive utility of carboxyhemoglobin for the diagnosis of HA in anemic dogs. Results: Carboxyhemoglobin (median [interquartile range]) differed between dogs with HA (7.7% [2.5%]) and non‐HA (3.6% [1.05]; P < .001) and dogs with HA and nonanemic dogs (3.5% [0.65%]; P < .001). No difference was detected between nonHA and nonanemic dogs. The area under the ROC curve for carboxyhemoglobin as predictor of HA in anemic dogs was 0.997 (95% CI, 0.99‐1.00). Three optimal cut‐off points were identified, including 5.05%, 4.55% and 4.85%, with corresponding sensitivity/specificity of 92.6%/100%, 100%/92.6% and 96.3%/96.3%, respectively. Neither carboxyhemoglobin nor any of the CBC or chemistry analytes were associated with survival. Conclusions and Clinical Importance: Carboxyhemoglobin proved an excellent predictor of HA in dogs and might constitute a useful, ancillary tool for diagnosing and monitoring hemolytic anemias.